2016
DOI: 10.1159/000446446
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Hypermethylation Profile Independently Predicts Biochemical Recurrence Following Radical Prostatectomy

Abstract: Purpose: Detection of DNA hypermethylation is emerging as a novel molecular biomarker for different malignancies. We intend to define whether a hypermethylation profile of patients with prostate cancer (PCa) predicts biochemical recurrence (BCR) after radical prostatectomy (RP). Material and Methods: Genome-wide methylation analysis was performed using the GoldenGate Methylation Cancer Panel-I (Illumina, Inc.) on 10 normal prostate tissues and 58 tumor samples from patients treated by RP followed for prostate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Evidence from these studies suggests that hypermethylation of PITX2 , GSTP1 , and APC is associated with more aggressive PCa and disease prognosis [ 11 , 12 ]. Some other prior studies have focused on larger sets of CpG sites across the genome and identified different panels of CpG biomarkers for distinguishing more from less aggressive prostate tumors [ 13 18 ]. For example, in a previous epigenome-wide analysis from our group, we identified a panel of methylation biomarkers for predicting metastatic-lethal PCa [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from these studies suggests that hypermethylation of PITX2 , GSTP1 , and APC is associated with more aggressive PCa and disease prognosis [ 11 , 12 ]. Some other prior studies have focused on larger sets of CpG sites across the genome and identified different panels of CpG biomarkers for distinguishing more from less aggressive prostate tumors [ 13 18 ]. For example, in a previous epigenome-wide analysis from our group, we identified a panel of methylation biomarkers for predicting metastatic-lethal PCa [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of GSTM2, Angulo et al [21] revealed that GSTM2 hypermethylation could be used to predict biochemical recurrence after radical prostatectomy, which suggested that epigenetic silencing of GSTM2 played an important role in involving biochemical recurrence. Plus, Ashour et al [22] demonstrated that GSTM2 was hypermethylated in PCa and was simultaneously methylated in 40.9% if the PCa, which revealed that epigenetic silencing of GSTM2 is a common event in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The second study using the GoldenGate Cancer Panel reported that a gene hypermethylation profile based on hierarchical clustering of patients (see Table 2 for details), as well as hypermethylation at individual markers GSTM2 and MCLY2 , independently predicted BCR risk. The concurrent methylation of the two markers was also associated with PCa death, however no further validation of the study findings in a separate independent cohort was conducted [ 130 ].…”
Section: Current State Of Prognostic Methylated Biomarkersmentioning
confidence: 99%
“…= average, CAPRA-S = Cancer of the Prostate Risk Assessment Score; CRPC = Castration-Resistant Prostate Cancer; GS = Gleason Score; HR = hazard ratio; IDC/C = Intraductal Carcinoma and Cribriform Architecture; M = multivariate analysis; NA = not applicable; non-sig = nonsignificant; ns = not specified; OR = odds ratio; pAUC = partial area under the cure; PCa = prostate cancer; PMR = percent methylated ratio; PSA = prostate- specific antigen; RT = radiotherapy; U = univariate analysis. Definitions: BCR: Biochemical recurrence: PSA elevations ≥ 0.2n g/mL post-RP, except [ 130 ] > 0.4 ng/mL and [ 131 ] > 0.07 ng/mL; clinical recurrence = local recurrence or metastatic relapse; good prognosis: organ-confined disease (pT2) and lack of BCR for at least 5 years; local recurrence: cancer observed on prostatic bed, confirmed by histological analysis of biopsies; metastatic relapse: metastatic deposits (visceral, bony metastasis) confirmed by positive biopsies or cT/bone scans; metastatic-lethal progression = metastatic relapse or PCa death; pathological T-stage: tumour staging based on pathological examination of surgically removed prostate tissue; PCa death: prostate cancer-specific death; poor prognosis: systemic presence of metastatic disease, indicated by recurrence within 3 years and no response to local radiation therapy; progression: either of BCR, metastatic relapse or PCa death; recurrence: either of BCR, local recurrence or metastatic relapse. a All studies are on prostate cancer tissues from radical prostatectomy, unless specified.…”
Section: Figurementioning
confidence: 99%